BANK MIKRO PERTANIAN SEBAGAI SOLUSI INOVATIF KEBIJAKAN PERBANKAN MENDUKUNG PERKEMBANGAN SEKTOR EKONOMI PRIORITAS BIDANG PERTANIAN - Khoirin Andi, Ahmad; Ubaidillah (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2022)
One focus of economic growth and employment is rural economic growth. The rural economic circle is a sector which is quite vital, because rural communities are a significant contributor to employment which is still polemic. The agricultural sector is a solution to answer these problems. By maximizing agricultural productivity, land management, supply of fertilizer and the availability of access to capital will increase the welfare of rural communities and open up large enough employment. In Segobang Village, Lici Kabupaen District, Banyuwangi, farmers synergized by forming farmer groups and then each group was accommodated into a Farmers Group Association (Gapoktan). The Farmers Group Association then affiliated to an organization that served as a business entity collecting and channeling funds in the form of farmer empowerment. In this study the methodology used is descriptive qualitative analytic, where the study of social and cultural phenomena in an atmosphere that takes place naturally (Faisal, 1990: 43)